Perspective of Carbon Nanotubes - El-Din Saleh, Hosam; Moawad Mohamed El-Sheikh, Said (IntechOpen, 2019)
Carbon nanotubes belong to new nanomaterials and have been known for almost 20 years, but their history is somewhat lengthier. They have been identified as promising candidates for various applications.High-temperature preparation techniques are conventional techniques for the synthesis of carbon nanotubes using arc discharge or laser ablation, but today these methods are being replaced by low-temperature vapor deposition techniques, since orientation, alignment, nanotube length, diameter, purity, and density of carbon nanotubes can be precisely controlled. The synthesis of carbon nanotubes by chemical vapor deposition on catalyst arrays leads to nanotube models grown from specific sites on surfaces. The controlled synthesis of nanotubes opens up interesting possibilities in nanoscience and nanotechnologies, including electrical, mechanical and electromechanical properties and devices, chemical functionalization, surface chemistry and photochemistry, molecular sensors, and interfacing with moderate biological systems.Carbon nanotubes are used in many applications due to their unique electrical, mechanical, optical, thermal, and other properties. Conductive and high-strength composite materials, energy saving and energy conversion devices, sensors, visualization of field emissions and sources of radiation, means for storing hydrogen, and nanoscale semiconductor devices, probes, and interconnections are some of the many applications of carbon nanotubes.